Cálculo de áreas de figuras planas e espaciais com aplicações ao ensino fundamental e médio - Custodio, Alessandro Luis [UNESP] (2015)
The purpose of this work is to assist the mathematics teacher through the detailed study about area of the plane figures and spatial figures seen in high schools. We present a very short historical account, as well as an analysis about text books and handouts of State São Paulo used in high school. There will be a theoretical foundation in which we will prove of the results about area and finally we will present some activities of the theme for high school